Soluble epoxide hydrolase inhibition preserves alveolar bone in experimental periodontitis with estrogen deficiency - Ritter, Charles; Silva Pacheco, Pedro; Mattos, Lila Batista Trajano; Soares, Mariana Quirino Silveira; Moreira, Debora Duarte; Rubira-Bullen, Izabel Regina Fischer; Duarte, Marco Antonio Hungaro; Van Dessel, Jeroen; Hammock, Bruce D.; Carbone, Laura; Clemente-Napimoga, Juliana Trindade; Abdalla, Henrique Ballassini; et al. (Frontiers in Immunology, 2025)
Osteoporosis and periodontitis are highly prevalent chronic conditions characterized by deregulated bone remodeling. Estrogen deficiency after menopause accelerates systemic bone resorption and also increases susceptibility to periodontal breakdown, resulting in a clinically relevant comorbidity that amplifies alveolar bone loss. Therapeutic strategies that target both systemic and local inflammatory mechanisms remain scarce. Soluble epoxide hydrolase (sEH) regulates the degradation of epoxyeicosatrienoic acids, lipid mediators with anti-inflammatory properties. Its inhibition stabilizes these mediators and has emerged as a promising approach in chronic inflammatory diseases. Here, we investigated whether pharmacological sEH inhibition could attenuate periodontitis exacerbated by estrogen deficiency. Female Wistar rats (8 weeks, 250 g) were assigned to Sham, OVX, PD, OVX + PD, or OVX + PD treated with the sEH inhibitor TPPU (1 mg/kg, oral). Experimental periodontitis was induced by ligature placement around the first lower molar and evaluated at 14 and 28 days for alveolar bone loss. Histological analyses were performed on mandibles (H&E and immunohistochemistry). Gingival biopsies and cervical lymph node were used for gene expression and protein level. Here, we demonstrated that estrogen deficiency aggravated ligature-induced periodontal destruction, as evidenced by greater furcation area, increased osteoclast numbers, elevated pro-inflammatory cytokines, and a higher RANKL/OPG ratio, alongside suppression of osteogenic markers. TPPU significantly reversed these changes by reducing bone loss, downregulating inflammatory cytokines, normalizing RANKL/OPG balance, and enhancing osteoblast-related gene expression. Furthermore, TPPU decreased immune activation in draining lymph nodes, indicating systemic effects. In conclusion, sEH inhibition by TPPU attenuates estrogen deficiency–associated periodontitis, representing a potential therapeutic strategy for postmenopausal periodontal bone loss.